Climate change, environmental justice, and socioeconomic inequalities in sport: a systematic literature review of research published between 2020 and 2025 - Anisa Sholiha Mia; Kristian Burhan; Rudyanto Rudyanto (Indonesian Institute For Counseling, Education and Therapy, 2025)
This systematic literature review summarises the evidence regarding the relationships between climate change, environmental justice, and inequality as regards organised sport, physical activity, and sport governance. A Scopus database of papers was built using a structured search and following the PRISMA 2020 guidance. Two independent reviewers conducted study screening and data extraction, achieving substantial agreement (Cohen's κ = 0.86). Methodological quality was assessed using the FICO framework, and findings were synthesized through thematic synthesis following Thomas and Harden. The search covered publications indexed in Scopus between January 2020 and March 2025.Altogether, 965 records were identified, 10 of which were eventually selected through screening and eligibility. Three different categories have appeared. Climate change effects such as extremely hot weather and the disappearance of winter sport opportunities are first on the list of the most severe and devastating ones. That is, the poorest countries, small island states, and disadvantaged people suffer the most as these communities have little or no possibility to protect themselves. Secondly, the sports governing bodies and other initiatives that pursue a sustainable development path, such as the Sustainable Development Goals or the Environmental, Social and Governance practices, will reproduce unjust distributions and procedural and recognition disparities if they do not take equity as a key issue explicitly. Third, unequal access to a variety of sporting facilities, green parks as well as clean and safe public places further worsens the disparity of people's health outcomes and sporting participation. The paper draws upon sport ecology, environmental sociology, and the capability approach as theoretical frameworks. In the closing remark, the authors point out major avenues for equitable adaptation, planning of inclusive sporting facilities, a just sports system, all of which can be further explored in Global South and other intersectional settings.